How do others think about my group? Adolescents’ meta-stereotypes about Turkish- and German-origin students’ subject-related German and general school competence - Haase, Jannika; Höhne, Elisabeth; Hannover, Bettina; McElvany, Nele; Zander, Lysann (Social psychology of education, 2024)
In Germany, Turkish-origin students face negative competence-related stereotypes held by different groups in society, including teachers at school. While a large body of research has examined stereotypes (i.e., other-stereotypes ) about immigrant students, little is known about their own competence-related meta-stereotypes , i.e., beliefs regarding the other-stereotypes that outgroup peers hold about them. The present study addresses this research gap by examining Turkish- and German-origin students’ meta-stereotypes about two dimensions of competencies not yet investigated, namely Turkish- and German-origin students’ subject-related German competence as well as their general school competence using a newly developed instrument combining verbal and non-verbal measures. These assessments are juxtaposed to the evaluations of a group of peers with other immigrant backgrounds (i.e., others’ meta-stereotypes ). In line with previous evidence, we found positive meta-stereotypes (as well as other- and others’ meta-stereotypes) towards German-origin students reported by all three groups. However, our study is the first that supports the existence of negative meta-stereotypes (as well as other- and others’ meta-stereotypes) towards Turkish-origin adolescents, again, among all participants. This pattern was particularly pronounced regarding the dimension of subject-related German competence. We discuss the findings’ potential relevance for students’ self-concepts and intergroup interactions in classrooms.